ANALYSIS OF LARGE-SCALE SIGNALS USING NOPOSITIONAL CODES RESIDUE CLASSES - Igor Anatol'evich Kalmykov; Andrey Valer'evich Dunin; Maxim Igorevich Kalmykov; Tatyana Aleksandrovna Gish (Современная наука и инновации, 2022)
The purpose of research is to improve the accuracy of performance of the large-scale analysis of signals. Achieving this goal is possible through the use of algebraic systems with the property of the ring and field.